North African Medicinal Plants Traditionally Used in Cancer Therapy - Alves-Silva, Jorge M.; Romane, Abderrahmane; Efferth, Thomas; Salgueiro, Lígia (Frontiers in Pharmacology, 2017)
Background: Cancer is a major cause of mortality worldwide with increasing numbers by the years. In North Africa, the number of cancer patients is alarming. Also shocking is that a huge number of cancer patients only have access to traditional medicines due to several factors, e.g. economic difficulties. In fact, medicinal plants are widely used for the treatment of several pathologies, including cancer. Truthfully, herbalists and botanists in North African countries prescribe several plants for cancer treatment. Despite the popularity and the potential of medicinal plants for the treatment of cancer, scientific evidence on their anticancer effects are still scarce for most of the described plants. Objective: Bearing in mind the lack of comprehensive and systematic studies, the aim of this review is to give an overview of studies, namely ethnobotanical surveys and experimental evidence of anticancer effects regarding medicinal plants used in North Africa for cancer therapy Method: The research was conducted on several popular search engines including PubMed, Science Direct, Scopus and Web of Science. The research focused primarily on English written papers published between the years 2000 and 2016. Results: This review on plants traditionally used by herbalists in North Africa highlights that Morocco and Algeria are the countries with most surveys on the use of medicinal plants in folk medicine. Among the plethora of plants used, Nigella sativa and Trigonella foenum-graecum are the most referred ones by herbalists for the treatment of cancer. Moreover, a plethora of scientific evidence qualifies them as candidates for further drug development. Furthermore, we report on the underlying cellular and molecular mechanisms. Conclusion: Overall, this review highlights the therapeutic potential of some medicinal plants as anticancer agents. The North African flora offers a rich source of medicinal plants for a wide array of diseases, including cancer. The elucidation of their modes of action represents an indispensable condition for the rational development of new drugs for cancer treatment. Furthermore, testing the anticancer activity in vivo and in clinical trials are warranted to explore the full therapeutic potential of North African plants for cancer therapy.